Jekyll and Hyde Leadership: A Multilevel, Multisample Examination of Charisma and Abuse on Follower and Team Outcomes. (November 2018) - Lee, Junghyun (Jessie); Wang, Gang; Piccolo, Ronald F.
Despite the independent treatment of the positive and negative sides of leadership in the literature, evidence suggests that the same leader may demonstrate both positive and negative leadership behaviors albeit with a different frequency (i.e., Jekyll and Hyde). What impacts would such opposing leadership styles jointly have on follower and team outcomes? To address this question, the current study examines the interactive impact of charismatic leadership and abusive supervision on individual- and team-level outcomes. Findings across three different samples gathered from the United States and South Korea suggest significant moderating roles of abusive supervision in the positive relationships of charismatic leadership with follower and team outcomes. This study highlights the importance of incorporating otherwise separate perspectives on leadership and provides insights into the boundary condition that impedes the effectiveness of charismatic leadership. Thus, we call for more research on integrative models of leadership that embrace different aspects of leader behaviors.